Movimento dos olhos e controle postural - Aguiar, Stefane Aline [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The control of stances such as the upright stance seems not to have a purpose in itself; this control could facilitate the execution of other simultaneous tasks, the so-called suprapostural tasks. The goal of this study was to determine the effects of saccadic eye movements on the control of posture. Twelve adult participants had their body oscillations analyzed while standing upright, for 70 s, in the postural conditions of feet apart and feet together, performing fixation in the central target or horizontal saccadic movements, in the conditions slow (0,5 Hz) and fast (1,1 Hz). The results showed that saccadic movements, independently of their frequency, strongly reduced trunk and head oscillations in the anterior-posterior (AP) axis. In this axis, there was an effect of feet position only in head oscillation. In the medio-lateral (ML) axis, the results showed a strong effect of feet position with body oscillation decreased in the condition of feet apart. The effect of the visual task in the ML axis occurred only for trunk oscillation, not reaching significance level in the pairewise comparisons. In the AP axis, the data corroborate a facilitatory explanation of the control of posture: the reduction in body oscillation limited the variations of the stimulus image projected on the retina, facilitating the execution of saccadic movements as compared to fixation. In the ML axis, the effect of reducing the basis of support was more evident than the effect of saccadic movements, suggesting that the available resources were used primarily for the postural task in detriment of the visual task. Additionally, aspects like attentional focus and sensory information pick up are discussed as mechanisms involved in this task

O controle de posturas como ficar em pé, parado parece não ter finalidade em si mesma; este controle pode facilitar a execução de outras tarefas simultâneas, as chamadas tarefas supraposturais. O objetivo deste estudo foi determinar os efeitos de movimentos sacádicos dos olhos sobre o controle da postura. Doze participantes adultos tiveram suas oscilações corporais analisadas enquanto permaneceram em pé, por 70 s, nas condições posturais de pés afastados ou pés unidos, executando uma fixação no alvo central ou movimentos sacádicos horizontais, nas condições lenta (0,5 Hz) e rápida (1,1 Hz). Os resultados mostraram que os movimentos sacádicos, independentemente da freqüência, reduziram fortemente as oscilações do tronco e da cabeça no eixo ântero-posterior (AP). Neste eixo, houve efeito da posição dos pés somente sobre a oscilação da cabeça. No eixo médio-lateral (ML), os resultados mostraram um forte efeito da posição dos pés com oscilação corporal diminuída na condição de pés afastados. O efeito da tarefa visual no eixo ML ocorreu apenas para a oscilação do tronco, não alcançando nível de significância na comparação aos pares. No eixo AP, os dados corroboraram uma explicação facilitatória do controle da postura: a redução da oscilação corporal limitou as variações da imagem do estímulo projetada na retina, facilitando a execução dos movimentos sacádicos em comparação à fixação. No eixo ML, o efeito da redução da base de apoio foi mais evidente do que o efeito dos movimentos sacádicos, sugerindo que os recursos disponíveis foram utilizados primeiramente para a tarefa postural em detrimento da tarefa visual. Adicionalmente, são discutidos aspectos como foco atencional e captação de informação sensorial como mecanismos envolvidos nesta tarefa
Keywords: Educação física - Estudo e ensino; Olhos - Movimentos; Equilibrio; Postura humana; Exercícios físicos; Musculos; Physical education and training Study and teaching